(untitled) (Research, Society and Development, 2021)
Stemodia maritima L., is a shrub of the Plantaginaceae family, with some biological activities already described, such as: larvicide, antimicrobial, and anti-inflammatory. Thus, the objective of this work was to evaluate the antioxidant, and gastroprotective activities of the ethyl acetate extract from S. maritima. The phytochemical profile was investigated through the quantification of total phenolic compounds, flavonoids, and CCD analysis. The toxicity of the extract was performed through cell viability using L929 line cell, and acute toxicity by the OECD Guide 423. The antioxidant activity was analyzed by the methods of reduction of the ferric ion (FRAP), total antioxidant activity (TAA), and the gastroprotective activity by the absolute ethanol-induced gastric ulcer model, with analysis of NO, MDA, GSH and MPO levels in the stomach tissues. In the phytochemical profile it was possible to identify the presence of flavonoids, triterpenes, steroids, mono, and sesquiterpenes. The extract was not cytotoxic against L929 lineage, maintaining cell viability above 70% at the doses tested, and in acute toxicity it did not show physiological changes indicative of toxicity compared to the control group. The extract presented antioxidant activity of 157.3 ± 9.7 mg equivalent of Trolox/g of extract in the FRAP method, and 50.0 ± 1.1 % by TAA. The ethyl acetate extract of S. maritima, at the doses tested, reduced the ulcerative lesion index compared to the injured control group, increased the levels of NO and GSH, and was able to decrease the concentrations of MDA and MPO, enhancing their gastroprotective activity.